REORIENTING LOCAL GOVERNMENT FUNCTIONS IN COASTAL SETBACK SPATIAL PLANNING TO FULFILL CONSTITUTIONAL ENVIRONMENTAL RIGHTS IN INDONESIA - I Gusti Ayu Eviani Yuliantari; Lita Tyesta Addy Listya W; Budi Ispriyarso (Awang Long Law Review, 2026)
Article 28H(1) of the 1945 Constitution affirms the right of every person to a good and healthy environment and, in doing so, places a binding constitutional duty on the State to ensure environmental protection through all instruments of public governance, including spatial planning. This research explores the enduring disconnect between the normative structure of Indonesia’s spatial planning regime and its practical application in coastal setback areas, with particular emphasis on the functions and responsibilities of local governments within the decentralization framework. Adopting a non-doctrinal socio-legal approach and employing a case study of South Bali, the study combines constitutional interpretation with empirical observations to evaluate how spatial governance practices shape the realization of environmental rights. The analysis demonstrates that spatial planning in coastal zones has not operated as an effective preventive mechanism, as development-led policies most notably those driven by tourism investment have consistently taken precedence over ecological protection, disaster risk reduction, and the preservation of public coastal access. In addition, governance changes following the enactment of the Job Creation Law reveal a growing tendency toward recentralization, which constrains the substantive decision-making capacity of local governments while simultaneously maintaining their formal accountability for environmental outcomes. This structural inconsistency gives rise to a form of constitutional failure by omission. Accordingly, the study argues for a fundamental reorientation of local government functions, repositioning spatial planning as a rights-based, precautionary, and participatory governance instrument grounded in ecological justice, constitutional accountability, and the integration of local wisdom, in order to restore its effectiveness in fulfilling constitutional environmental rights.